Responsible Sourcing of Materials Required for a Resource Efficient and Low-carbon Society - Mancini, Lucia; Nuss, Philip (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Understanding future supply and demand of raw materials and the associated environmental and social implications is essential to supporting the transition towards greenhouse gas neutrality by 2050. In this Special Issue, we present a range of research papers with a focus on future outlooks of material supply and use, the consideration of associated environmental and social implications, and issues of raw material criticality and a circular economy. These are complemented by an editorial paper that provides, amongst other aspects, an overview of the corresponding policy and institutional framework. Knowledge of materials availability, their use patterns in modern economies, and associated environmental and social trade-offs is essential for informed decision-making in support of the necessary transition towards more resource-efficient and greenhouse-gas-neutral societies in the coming years.